TEMPERATURE RECONSTRUCTION FOR ARCTIC GLACIERS - Nagornov O.V.; Konovalov Y.V.; Tchijov V. (My University, 2006)
Numerous data indicate discernible warming of the Northern Hemisphere in the 20th century especially at high latitudes. Summer melting at the surface of Arctic glaciers is likely to increase this warming. To verify this phenomenon, we reconstruct the past temperatures of the Arctic ice caps at their surface and at the 10 m depth. The reconstructions are made for two Arctic ice caps (Austfonna and Akademii Nauk) by means of the inversion of the measured temperature-depth profiles. In addition, we use the measured oxygen–isotope ratio and the melt feature index as input data. We find that the present ice temperature is the highest over the last 1000 years, while the lowest temperature occurred in the 1700s. The surface temperature variations of Akademii Nauk (Severnaya Zemlya) and Austfonna (Svalbard) Ice Caps exceed the average Arctic temperature anomalies over the last 150 years by 6 to 7 °C.